Patient Safety Status In Hospitals Of Tehran-Patient Safety Friendly Hospitals Standards: 2013 - Zohreh Mazhari; Amin Adel (Tehran University of Medical Sciences, 2015)
Background and Aim: Patient safety standards are a set of requirements that are crucial for the implementation of patient safety in hospitals. Process evaluation of patient safety in hospitals has developed a mechanism to determine the level of patient safety. This mechanism can also start a program aimed at improving patient safety and evaluate programs that are being used.  Materials and Methods: This analytic study was to determine the status of compliance with critical safety standards for patients in 10 hospitals in Tehran in May to August 2013. All segments of the population are hospitals in Tehran and were selected randomizely. Research tool was a checklist and its validity and reliability was approved. SPSS version 16 software for data evaluation and statistical techniques were used.  Results: According to the data of this study, the mean level of standards was 76.69%. Also, according to the average standards, the highest level of respect in Group D (80.40%) and minimum standards in group B (56.33%) were observed. Hospitals that had more than 400 beds (71.73%) and hospitals with less than 200 beds (66.22%) have been met with standards.  Conclusion: According to these results, we can increase patient safety standards of our country by establishing the culture of patient safety, patient-centered approach to service delivery, training of staff and patients and legal barriers.